Penerapan Metode Pembelajaran Diskusi Tipe Buzz Grup Untuk Meningkatkan Hasil Belajar Mahasiswa - Kholida Ismatulloh; Khaerus Syahidi (Kappa Journal, 2019)
The research title "The Implementation of Buzz Group Discussion learning method to improve student physics learning outcomes" aims to improve physics learning outcomes in second semester of  Informatics Education students on material quantities and measurements. This type of research is a quantitative type of experiment, with a population of Informatics Education students, the research subject are semester 2 of Informatics Education taking 46 students consisting of 2 classes there are 2A and 2B. The results of the study experienced an increase in student physics learning outcomes with class averages of 76.25 and 75.65, previously at 72.45 and 70.35 of the average value had increased by 20%. The application of the discussion method of group buzz learning not only affects student learning outcomes but also motivation and interest in learning increases because in this method teamwork is highly prioritized, causing other group members to be active and courageous in expressing opinions when taking responsibility for answers in front of the class . The use of this method can reduce the problems that exist especially in learning physics on material quantities and measurements.